Subjective well-being and the family: Results from an ordered probit model with multiple random effects - Rainer Winkelmann (University of Zurich, Socioeconomic Institute, 2004)
The previous literature on the determinants of individual well-being has failed to fully account for the interdependencies in well-being at the family level. This paper develops an ordered probit model with multiple random effects that allows to identify the intrafamily correlation in well-being. The parameters of the model can be estimated with panel data using Maximum Marginal Likelihood. The approach is illustrated in an application using panel data for the period 1984-1997 from the German Socio-Economic Panel in which both inter-generational and intra-marriage correlations in well-being are estimated.
Keywords: C23; C25; I31; J19; 330; ordered probit model; error components; German Socio-Economic Panel; Lebensqualität; Familie; Familiensoziologie; Schätzung; Deutschland; Probit-Modell